2021
DOI: 10.3389/fcell.2021.682574
|View full text |Cite
|
Sign up to set email alerts
|

MiR-302a Limits Vascular Inflammation by Suppressing Nuclear Factor-κ B Pathway in Endothelial Cells

Abstract: The inflammatory response of endothelial cells accelerates various vascular diseases. MicroRNAs (miRNAs) participate in diverse cellular processes during inflammation. In the present study, we found that miR-302a is an effective suppressor of vascular inflammation in endothelial cells. It was revealed that miR-302a exhibited a lower level in a lipopolysaccharide (LPS)-induced mouse model and in patients with vascular inflammatory disease. Genetic haploinsufficiency of miR-302 aggravated the LPS-induced vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…In the CRC cell lines, RAD51-AS1 functioned as a competing endogenous RNA (ceRNA) for sponging miR-29b-3p and miR-29c-3p . An In vitro studies on miR-361-5p and miR-302a, results showed their inhibitory effect on the NF-κB signaling pathway [73,74].our studies also indicate a 2.465 fold overexpression in blood samples of UC patients compare to controls. Based on bioinformatics results, its instigating effect on NF-κB pathways maybe related to regulatory target miRNAs such as miR-361-5p and miR-302a.…”
Section: Discussionsupporting
confidence: 64%
“…In the CRC cell lines, RAD51-AS1 functioned as a competing endogenous RNA (ceRNA) for sponging miR-29b-3p and miR-29c-3p . An In vitro studies on miR-361-5p and miR-302a, results showed their inhibitory effect on the NF-κB signaling pathway [73,74].our studies also indicate a 2.465 fold overexpression in blood samples of UC patients compare to controls. Based on bioinformatics results, its instigating effect on NF-κB pathways maybe related to regulatory target miRNAs such as miR-361-5p and miR-302a.…”
Section: Discussionsupporting
confidence: 64%
“…MiR-302 is involved in Treg differentiation that is aided by macromolecular proteins. 55 By targeting IL-1 receptor-associated kinase 4, MiR-302a reduces vascular inflammation by blocking nuclear factors in endothelial cells' nuclear translocation. This reduces the phosphorylation of kinase complex I and inhibitor.…”
Section: Mir-302/367 Cluster and Inflammationmentioning
confidence: 99%
“…This reduces the phosphorylation of kinase complex I and inhibitor. 55 Brain hemorrhage induces microglia activation and inflammatory cytokine release, leading to brain inflammation. In vivo investigations, adhesion molecules and inflammatory cytokines are increased in the absence of miR-367, whose expression is downregulated in the serum of patients with coronary heart disease.…”
Section: Mir-302/367 Cluster and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-302 cluster inhibits angiogenesis by targeting VEGFA [33] and has also been involved in the reduction of vascular inflammation according to the binding sequence by interaction with zinc finger protein 91 (ZFP91). ZFP91 activates the hypoxia-induced factor 1α (HIF-1 α), promoting cell proliferation [34,35].…”
Section: Introductionmentioning
confidence: 99%